Respuesta :
Answer:
[tex]x=3-\sqrt{6},x=3+\sqrt{6}[/tex]
Step-by-step explanation:
we are given equation as
[tex]2x^2-12x=-6[/tex]
Since, we have to solve it by using complete square
so, firstly we will complete square
and then we can solve for x
step-1:
Factor 2 from both sides
[tex]2(x^2-6x)=-3\times 2[/tex]
step-2:
Simplify it
[tex]x^2-6x=-3[/tex]
step-3:
Add both sides 3^2
[tex]x^2-6x+3^2=-3+3^2[/tex]
now, we can complete square
[tex](x-3)^2=6[/tex]
step-4:
Take sqrt both sides
[tex](x-3)=-\sqrt{6},(x-3)=\sqrt{6}[/tex]
step-5:
Add both sides by 3
we get
[tex]x=3-\sqrt{6},x=3+\sqrt{6}[/tex]